Pemetaan Tingkat Kemiskinan di Provinsi Jawa Tengah Berdasarkan Kabupaten/Kota dengan Metode K-Medoids - Fitriani Dwi Ratna Sari; Sotya Partiwi Ediwijojo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Poverty describes a condition of lack of ownership and low income, or in more detail describes a condition that basic human needs cannot be fulfilled, namely food, shelter, and clothing. In the last ten years, Central Java's poverty reduction performance has had its ups and downs, with rural poverty still dominating. The purpose of this research is to conduct a mapping analysis in the form of clusters on the number of poverty levels in districts or cities in the province of Central Java using artificial intelligence techniques. Given that Central Java is the third most populous province after West Java and East Java. This needs to be done in order to obtain a macro picture of the poverty level over the last few years through regional mapping. The dataset used is sourced from the Central Java Statistics Agency (BPS) website on the subject of the number of poor people (thousands of people) in 2017-2019. The solution given in conducting mapping in the form of clusters is the K-Medoids method which is part of clustering data mining. The number of clusters used are high and low clusters in mapping the number of poverty levels. The mapping analysis process uses the help of RapidMiner software. The results showed that 6 provinces (17%) were in the high cluster and 29 provinces (83%) were in the low cluster. The final centroid values for each cluster are {293.2, 309.2, 343.5} in the high cluster (cluster_1) and {18.6, 19.4, 20.1} in the low cluster (cluster_0). The results of the mapping can be useful information for tackling the poor where the high cluster (cluster_1) is a priority for the government in the province of Central Java, namely Cilacap Regency, Banyumas Regency, Kebumen Regency, Grobogan Regency, Pemalang Regency, Brebes Regency